2012
DOI: 10.1089/chi.2012.0085.blan
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Go to the Park Today: The Role of Parks in Obesity Prevention and Improving the Public’s Health

Abstract: Let's go to the park today! This familiar phrase is heard routinely throughout the year in many U.S. households. Access to parks, trails, open spaces, and recreational facilities not only provides increased opportunities for children and adults to play and be physically active, but these venues also influence other behaviors. As the health and wellbeing of our children are impacted by the daily environment in which they live, learn, and play, the use of parks and other recreation spaces as a healthful venue is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…Parks are an important public space for promoting health, especially in urban settings with limited open space (10), not only through physical activity but also through access to healthful food. Parks are the second largest public provider of food to children in…”
Section: Introductionmentioning
confidence: 99%
“…Parks are an important public space for promoting health, especially in urban settings with limited open space (10), not only through physical activity but also through access to healthful food. Parks are the second largest public provider of food to children in…”
Section: Introductionmentioning
confidence: 99%
“…The larger buffer has a 1,000m radius and covers a circular area of approximately 3,140,000m 2 . The smaller buffer has a 250m radius and covers an area of approximately 200,000m 2 . Given that both of these buffers have 50% green cover, the 1,000m buffer would include 1,570,000m 2 (nearly 400 acres) of greenspace, but the 25m buffer would only include 100,000m 2 (approximately 25 acres) of greenspace.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller buffer has a 250m radius and covers an area of approximately 200,000m 2 . Given that both of these buffers have 50% green cover, the 1,000m buffer would include 1,570,000m 2 (nearly 400 acres) of greenspace, but the 25m buffer would only include 100,000m 2 (approximately 25 acres) of greenspace. Because the smaller buffer analysis does not describe green cover beyond this relatively small area, it cannot evaluate whether the broader neighborhood includes those additional 1,470,000m 2 of green cover represented in the 1,000m buffer analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public parks and playgrounds have been found to be highly important for the development of such skills for various reasons. Firstly, many studies have conclusively demonstrated that access to playgrounds or parks has a positive correlation with the amount of physical activity of the child (Blanck, Allen, Bashir, Gordon, Goodman, Merriam, & Rutt, 2012). It has also been found to be positively associated with the mental development of the child, as physical activity is often associated with improved mental health (Sherer, 2003).…”
Section: Introductionmentioning
confidence: 99%